PENGARUH CEO WANITA TERHADAP CASH HOLDING PERUSAHAAN - Suherman Suherman (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract: The objective of this research is to examine the effect of the existance offemale CEOs on corporate cash holdings. Sample of this research consists of 56companies listed on LQ45 index between 2012 and 2015 (136 observation).Controlling for firm size, leverage, board size, dividend, liquidity and growth, the resultshows that the existance of female CEOs significantly affect corporate cash holdings.This implies that female CEOs are more conservative than their male counterparts.Keywords: Female CEOs, gender diversity, corporate cash holding